Normalised complexity metric for manoeuvering target tracking - Bing Liu; Xiao Jing Shen (Electronics Letters, 2021)
Abstract Manoeuvering target tracking is a challenging problem for filter design in a variety of tracking systems. However, how to quantify the complexity of this problem is seldom studied. In this paper, a normalised complexity metric for manoeuvering target tracking called relative difficulty to Kalman filter is defined as the ratio between maximum tolerance error of positional estimation and its requirement precision of positional measurement. It can be employed as an indicator of the difficulty of designing an advanced filter to satisfy the tracking requirement. Analytical expression of RD2KF in three‐dimensional space is derived. Two typical tracking examples show that RD2KF is affected by manoeuver intensity, data rate and the required precision of the tracking mission.